2022
DOI: 10.1093/ibd/izac035
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab and Vedolizumab Are Not Associated With Subsequent Cancer in IBD Patients with Prior Malignancy

Abstract: Background There is little data regarding the risk of new or recurrent cancer in patients with inflammatory bowel disease (IBD) and a prior history of cancer who are exposed to ustekinumab or vedolizumab. We assessed the risk of subsequent cancer in patients exposed to these agents. Methods We performed a retrospective cohort study of patients with IBD and a history of cancer at an academic medical center between January 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…-5.41] [312]. Whilst safety signals are thus far reassuring, the numbers and duration of follow up are too limited to draw firm conclusions.…”
mentioning
confidence: 99%
“…-5.41] [312]. Whilst safety signals are thus far reassuring, the numbers and duration of follow up are too limited to draw firm conclusions.…”
mentioning
confidence: 99%
“…Although a longer follow up is required, evidences suggest that their use does not increase the overall cancer risk in IBD ( 47 , 48 ).In patients with a present or prior history of cancer, one retrospective study reported that vedolizumab does not increase the risk of new/recurrent cancer ( 49 ). Comparable findings were observed using vedolizumab or ustekinumab in IBD patients with prior malignancy ( 50 ). Additional data and a longer follow up is required for assessing the risk of new/recurrent cancer using these more immunomodulators, and particularly tofacitinib (pan-JAK inhibitor) ( 51 ) in IBD patients with a history of cancer.…”
Section: Personalizementioning
confidence: 76%
“…To answer how best to treat patients with previous cancers, we need to study patients with previous cancers. Retrospective analysis of patients with IBD with previous cancer receiving anti-TNF, ustekinumab or vedolizumab44–46 and pooled data on cancer recurrence in patients with inflammatory conditions receiving immunosuppression57 go some way to provide reassurance that we may overestimate treatment-related risks. However, we must recognise the potential for treatment selection bias in retrospective data when the factors determining that treatment choice are unknown; those seen most at risk of recurrence may not have been given perceived higher-risk treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to anti-TNF or no immunosuppression. Additional reassurance is suggested by a further two recent studies that have reported that use of ustekinumab or vedolizumab45 or vedolizumab or anti-TNF46 for IBD therapy in patients with a prior history of cancer does not appear to be associated with an increased risk of new or recurrent cancer.…”
Section: Introductionmentioning
confidence: 99%